Peran Teks dan Konteks Dalam Penafsiran Filsafat: Menelusuri Keragaman Mazhab Pemikiran - Saumantri, Theguh (Indonesian Journal of Islamic Theology and Philosophy, 2025)
Abstract; The interpretation of philosophical texts is always closely tied to social, historical, cultural, and biographical contexts, which influence how these texts are understood and accepted by readers. This study aims to analyze the role of texts and context in philosophical interpretation, as well as how their interaction gives rise to the diversity of existing schools of thought. Using a descriptive qualitative approach, this research analyzes philosophical texts from various intellectual traditions, both Western and Eastern, through an in-depth literature review. The findings of the study show that although philosophical texts contain profound and universal meanings, they can be interpreted in different ways depending on the social, political, and cultural context of the reader, resulting in various philosophical schools such as rationalism, empiricism, existentialism, and others. Academically, this research contributes to enriching the study of philosophy, particularly in understanding the dynamics of diverse text interpretations, as well as their relevance in religious and social studies. The study also emphasizes the importance of understanding context in reading philosophical texts to obtain a more contextual and inclusive understanding of the development of philosophical thought. Keywords: Context; Interpretation; Philosophical Texts; Schools of Philosophy.   Abstrak; Penafsiran teks filsafat selalu terikat erat dengan konteks sosial, sejarah, budaya, dan biografis, yang memengaruhi cara teks tersebut dimaknai dan diterima oleh pembaca. Penelitian ini bertujuan untuk menganalisis peran teks dan konteks dalam penafsiran filsafat, serta bagaimana interaksi keduanya melahirkan keragaman mazhab pemikiran yang ada. Dengan menggunakan pendekatan kualitatif deskriptif, penelitian ini menganalisis teks-teks filsafat dari berbagai tradisi pemikiran, baik dari Barat maupun Timur, melalui kajian pustaka yang mendalam. Hasil penelitian menunjukkan bahwa teks filsafat, meskipun mengandung makna yang mendalam dan universal, dapat ditafsirkan secara berbeda-beda bergantung pada konteks sosial, politik, dan budaya pembaca, yang menghasilkan perbedaan aliran filsafat seperti rasionalisme, empirisme, eksistensialisme, dan sebagainya.  Secara akademik, penelitian ini memberikan kontribusi dalam memperkaya kajian filsafat, khususnya dalam memahami dinamika interpretasi teks yang beragam, serta relevansinya dalam studi keagamaan dan sosial. Penelitian ini juga menggarisbawahi pentingnya memahami konteks dalam pembacaan teks filsafat untuk memperoleh pemahaman yang lebih kontekstual dan inklusif terhadap perkembangan pemikiran filosofis. Kata Kunci:   Konteks; Mazhab Filsafat; Penafsiran; Teks Filsafat.